PENGEMBANGAN RPP DENGAN KERANGKA ELPSA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI LOGIKA MATEMATIKA SISWA KELAS X MA NW SEPIT TAHUN PELAJARAN 2016/2017 - Supiani, Supiani; Sanapiah, sanapiah; Juliangkary, Eliska (Media Pendidikan Matematika, 2017)
This development research aims to produce a mathematics lesson plan using ELPSA framework in order to improve students problem solving abilities and to know the quality of lesson plan based on validity and practical aspects. The type of this research is development with ADDIE model. The subject of this research is the development of lesson plan using ELPSA framework on math logic material. The instruments used are questionnaire for aspects of validity, teacher evaluation sheet and student response questionnaire for practicality aspect, and test of learning result to know problem solving ability. The quality of lesson plan validity assessed from material aspect get percentage score of 85% included in very good category. Aspects of media get a percentage score of 89% included in the category very well. So the lesson plan is said to be valid. The quality of the practicality of lesson plan based on teacher evaluation sheet gets the average percentage score of 85.5% included in very good category. So the lesson plan has a practical quality, based on the questionnaire of student responses obtained average student score is 72.5 included in the good category, which means the lesson plan has a practical quality. Problem solving abilities in terms of student test result based on pre-test and post-test results increased with average score from 54.3 to 85. The results of this study indicate that the lesson plan that developed with ELPSA framework can improve problem solving ability and it has been said is feasible to be used in the learning process in SMA/MA using KTSP Curriculum because it meets the criteria of lesson plan quality (validity and practical).